Effect of caffeine on free-throw performance in college-aged basketball players - Tan, Zhi Sen (2019)
In the sporting world of basketball, free-throw shooting has always been known to be a vital component of the game. Besides constant practice to improve the technical aspect of it, supplements such as caffeine may be consumed to improve the performance of free throw shooting. The purpose of this study was to investigate the effects of caffeine on free-throw shooting performance in college-aged basketball players. 21 participants were recruited for the study, including 12 males (23.1 ± 1.9 years; 180.1 ± 8.8 cm; 77.1 ± 12.4 kg) and 9 females (22.1 ± 1.3 years; 167.2 ± 9.2 cm; 65.2 ± 10.2 kg). Participants ingested 6 mg per kg of body mass of either (a) caffeine or (b) maltodextrin as placebo. They repeated five sets of six sideline to sideline sprints of a basketball court and shot two free-throws after 60 min of caffeine absorption. Each set was interspaced with 2 min of rest. Heart rate and RPE were also recorded after the sprints. Caffeine did not improve the accuracy of free-throws (caffeine = 6.06 ± 1.73 vs. placebo = 5.50 ± 2.04; p = 0.336) and had no effects on RPE (caffeine = 13.5 ± 2.6 vs. placebo = 13.6 ± 2.7; p = 0.57) although caffeine increased heart rate compared to placebo (caffeine = 162.2 ± 10.4 vs. placebo = 158 ± 12.3; p = 0.015). The ingestion of 6 mg of caffeine per kg of body mass did not improve free-throw shooting performance.